Poly(vinyl alcohol) with sulfonic acid groups as catalyst for the alpha-pinene alkoxylation - Castanheiro, J (2012)
The alkoxylation of a-pinene was carried out over poly(vinyl alcohol) containing sulfonic acid groups, as catalyst. The main product of a-pinene alkoxylation was a-terpinyl methyl ether being also formed bornyl methyl ether, fenchyl methyl ether, limonene and terpinolene as by-products. The absorption band at 1037 cm-1 in the FTIR spectrum of PVA_SSA40 (PVA membrane containing 40% of –OH groups esterified with SSA) which does not appear in the spectrum of PVA, indicates the presence of the sulfonic acid groups. The catalytic activity of PVA with sulfonic acid groups increases when the amount of sulfosuccinic acid used in the polymer crosslinking is increased from 5% to 40%. However, when the crosslinking degree increases from 20% to 40%, the conversion of a-pinene increases only slightly. Good values of selectivity to a-terpinyl methyl ether were obtained over poly(vinyl alcohol) with sulfonic acid groups. A simple kinetic model, which fits experimental concentration data quite well, was developed.